Fe+3-montmorillonite K10 as an Efficient Reusable Heterogeneous Catalyst for the Grind Mediated Synthesis of 14-aryl-14H-dibenzo [a,j]xanthenes - Z. Fekri, Leila; Nikpassand, Mohammad; S. Fard, Hajar; Marvi, Omid (Letters in Organic Chemistry, 2016)
Background: Xanthenes are an important class of organic compounds and have also received significant attention due to their wide range of pharmacological activities such as antibacterial, antiviral, antiinflammatory activities, antagonists for the paralyzing action of zoxazolamine and efficiency in photodynamic therapy, a well-known method for controlling the localized tumors. Natural sources are also rich of xanthene compounds. Popularly known pigments, santalin have been isolated from plant species. Furthermore, these compounds can be emerged as pH-sensitive fluorescent materials for visualization of biomolecules, in laser technologies and as dyes. There are several reports in the literature for the synthesis of xanthenes such as alkylations of heteroatoms, cyclodehydrations, cyclocondensations between 2-hydroxyaromatic aldehydes and 2- tetralone, trapping of benzynes by phenols and intramolecular phenyl-carbonyl coupling reactions of benzaldehydes and acetophenones bearing tethered carbonyl chains in the presence of hexamethylphosphoramide and SmI2. Other methods for the synthesis of xanthenes include the reaction of formamide with β-naphthol, carbon monoxide, and 1- hydroxymethyl-naphthalen-2-ol. Methods: procedure a: A mixture of substituted benzaldehyde, 2-naphtol and Fe+3-montmorillonite K10 was mixed. After completion of the reaction, the product was solved in CHCl3 (3x10 mL) and insoluble catalyst was removed by filtration. The organic phase including the product and chloroform was evaporated under vacuum. The resulting crude material was purified by recrystallization from EtOH to afford pure products. procedure b: A mixture of substituted benzaldehyde, phenylhydrazine and Fe+3-montmorillonite K10 were added to a mortar and the mixture was pulverized with a pestle. After completion of the reaction, 2-naphtol was added to the consulting mixture and pulverized with a pestle. The organic phase including the product and chloroform was evaporated under vacuum. The resulting crude material was purified by recrystallization from EtOH to afford pure products. Results: As part of our going interest for the development of efficient and environmentally friendly procedures for the synthesis of heterocyclic and pharmaceutical compounds, we wish to report the first grind mediated synthesis of some derivatives of xanthenes using catalytic amount of Fe+3-montmotillonite. Conclusion: In conclusion, we have investigated the Fe+3-montmorillonite K10 under grinding as a mild and efficient catalyst for the synthesis of substituted 14-aryl-14H-dibenzo [a,j]xanthenes. The remarkable advantages offered by this method are: catalyst is inexpensive, non-toxic, easy handling and reusability, simple work-up procedure, short reaction time, high yields of product with better purity and green aspect by avoiding toxic catalyst and hazardous solvent.
Keywords: grind